APLIKASI PENGENALAN OBJEK WISATA KEPULAUAN RIAU MENGGUNAKAN METODE SOFTWARE DEVELOPMENT LIFE CYCLE - Rosmawati, Rosmawati; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2023)
The Riau Archipelago is a place that has many tourist objects, one of which is in Batam City. Batam City is one of the largest cities in the Riau Archipelago Province, strategically located very close to international waterways, direct widening with the Singapore Strait and the Malaysia Strait. Tourism object is everything that exists in a tourist destination area which is an attraction so that people want to come to visit that place, all places or natural conditions that have tourist resources that are built and developed so that they have an attraction and are cultivated as a place to visit. traveler. However, currently there is no application that helps the public to introduce tourist objects and forms of marketing or marketing tourism objects in Batam City for foreign tourists is very difficult. So with this Android-based application for recognizing tourist objects in the Riau Islands to make it easier or to get to know tourist objects in the Riau Islands, and to make it easier to find locations for tourist objects in the Riau Islands. Its creation in mobile form aims to make it easy to carry anywhere. with this an application will be created using Adobe Animate. This research method uses the SDLC (Software Development Life Cycle) method with the aim of introducing natural tourism objects in the Riau Archipelago and the design uses UML (Unified Modeling Language).